Rebranding Bawang Merah Goreng Sebagai Upaya Peningkatan Kualitas Bawang Merah Di Desa Musir Kidul - Siti Mi’Danur Rahmah; Aufa Izzuddin Baihaqi (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Product rebranding activities as an effort to improve the quality of shallot products in Musir Kidul village, Rejoso District, Nganjuk Regency, which is one of the activities aimed at the people of Musir Kidul Village to gain more knowledge about rebranding and also diversification of fried shallot products. Previously, the Shallot UMKM managed by Puspita Makmur Nganjuk had not innovated products but only sold shallots. Here we assist Shallots SMEs to diversify their products into fried shallots and also rebranding from a brand perspective, choosing the right brand that is easy for consumers to remember has an effect on product sales. The BARENG DIO brand ((Mas Dio's Fried Onion) is preferred as a fried shallot brand because it is easy to remember because it uses the name of the owner.